1976
DOI: 10.1083/jcb.71.1.280
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of transformation, cell density, and growth control to the cellular distribution of newly synthesized glycosaminoglycan.

Abstract: Mouse 3T3 cells and their Simian Virus 40-transformed derivatives (3T3SV) were used to assess the relationship of transformation, cell density, and growth control to the cellular distribution of newly synthesized glycosaminoglycan (GAG). Glucosamine-and galactosamine-containing GAG were labeled equivalently by [all]-glucose regardless of culture type, allowing incorporation into the various GAG to be compared under all conditions studied. Three components of each culture type were examined: the cells, which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
46
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…It also suggests that both of these components are under a similar type of control. Indeed, several studies have shown that the synthesis of hyaluronate is also much greater in proliferating cells as compared with nonproliferating cells (4,15), again paralleling what we have observed with the hyaluronate receptor.…”
Section: Discussionsupporting
confidence: 72%
“…It also suggests that both of these components are under a similar type of control. Indeed, several studies have shown that the synthesis of hyaluronate is also much greater in proliferating cells as compared with nonproliferating cells (4,15), again paralleling what we have observed with the hyaluronate receptor.…”
Section: Discussionsupporting
confidence: 72%
“…The basal lamina may contain specialized collagen types (Kefalides, 1978), specific glycoproteins (Timpl et al, 1979), hyaluronic acid (Cohn et al, 1976), and proteoglycans (Bernfield et al, 1972;Kanwar and Farquhar, 1979; Hassell et al, 1980), but little is known about the mechanisms that control its assembly.…”
mentioning
confidence: 98%
“…They have been found in association with cell surfaces (1)(2)(3)(4)(5), intracellular organdies (6,7), and extracellular matrices (especially basement membranes) (8)(9)(10)(11), and have been proposed to participate in a variety of functions such as cell-cell interactions (12), cell migration (13), and cell adhesion (14,15). HSPGs isolated from different sources have distinct structures in terms of their overall size (70-400 kD) and the size of their glycosaminoglycan chains (14-70 kD).…”
mentioning
confidence: 99%